Molecular characterization and antifungal susceptibility of Aspergillus collected in indoor settings - Simões, Daniela (2018)
The exposure to Aspergillus conidia is an increased risk factor for the development of respiratory symptoms, such as asthma, in occupational and non-occupational settings. Aspergillus identification should be based on molecular methods as there are species with similar morphology but distinct at the molecular level (cryptic species), with variable antifungal susceptibility profiles. The aim of this study was to perform the molecular identification of Aspergillus species collected from different occupational and non-occupational settings. Due to the emergence of azole-resistance in A. fumigatus, the susceptibility of the collected Fumigati isolates was determined.